Synthesis and expression of caf1 gene encoding F1 antigen of Yersinia pestis - Hà, Nguyễn Thị Thu; Minh, Nguyễn Phượng; Tài, Lê Trọng; Dũng, Phạm Tiến; Hòa, Lê Quang (Vietnam Journal of Biotechnology, 2016)
Yersinia pestis is the etiologic agent of plague, one of the most deadly infectious diseases described in the history of humanity. It was responsible for millions of deaths all over the world. Yersinia pestis also can be used as a highly lethal biological potential weapon. For plague diagnosis in humans as well as to detect Y. pestis in the environment, fraction 1 capsular antigen (F1) of the bacteria was usually used as a good marker. The aim of this study is to produce Y. pestis F1 antigen to serve as a material for development of immunochromatographic test strips for rapid detection of Y. pestis. Because of the difficulty in Y. pestis culture for DNA extraction as well as F1 antigen production, we artificially synthesized the target caf1 coding for F1 antigen for expression in Escherichia coli. After the codon optimization step, caf1 was synthesized by “gapless” PCR using 22 overlaping oligonucleotides cover the complete sequence of this gene. The sequencing result showed that we successfully synthesized the target gene. In total 6 clones sequence, there are 2 clones sequence which were 100% identity with reference sequence. The target sequence was then introduced into pET-52b(+) vector and expressed in E. coli BL21 (DE3) in the form of (His)10 affinity tag fusion. As the result of SDS-PAGE, the recombinant protein Caf1 of 18 kDa was highly expressed in E. coli as inclusion body form and was purified by His-tag affinity chromatography. The recombinant Caf1 was then confirmed by Western blot with His-tag antibody.